PROFESIONALISASI DESA ADAT DALAM PENGELOLAAN DAYA TARIK WISATA ALAM SANGEH MONGKEY FOREST DI BADUNG - Ida Ayu Tary Puspa; Putu Riska Wulandari; I Gusti Made Adi Satriawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Tourism has become one of the strategic sectors in promoting economic growth and preserving cultural heritage in Bali. Within this context, the Sangeh Traditional Village plays an important role in managing the Sangeh Monkey Forest as a natural tourism attraction that integrates environmental conservation, local culture, and community-based values. Despite its considerable potential, the management of tourism destinations based on traditional village institutions continues to face challenges related to the professionalism of human resources, the consistent implementation of governance standards, and the sustainability of management practices. This study aims to analyze the tourism potential of Sangeh Monkey Forest, examine the professionalization of its management, and evaluate the role of the Sangeh Traditional Village in maintaining a balance between cultural preservation, environmental protection, and community welfare. The research employed a descriptive qualitative approach and was conducted at the Sangeh Monkey Forest Tourism Attraction in Badung Regency, Bali. Informants were selected purposively, including tourism managers, traditional village officials, local community members, and visitors. Data were collected through observation, interviews, documentation, and literature review, while qualitative analysis was carried out through data reduction, data presentation, and conclusion drawing. The validity of the findings was strengthened through source and technique triangulation. The results reveal that Sangeh Monkey Forest possesses significant tourism potential, supported by its natural landscape, cultural values, adequate facilities, accessibility, and diverse tourism activities. The Sangeh Traditional Village has a strategic role in preserving local wisdom and ensuring that tourism development contributes to community welfare. However, management is still constrained by limited professional human resource practices, inconsistent application of standard operating procedures, and a staffing system that largely relies on kinship considerations. Therefore, strengthening organizational governance, improving human resource capacity, and implementing professional management standards are essential to achieving effective, accountable, and sustainable tourism management.